Rehabilitation device with stretching function for neurology department - GAO HUA; MAO JIEPING; FU GUIRONG; YUAN WEI (2022)
The neurology rehabilitation device with the stretching function comprises a nursing bed body, a first groove is formed in the upper surface of the nursing bed body in a penetrating mode, a back plate is rotatably installed in the first groove, an electric push rod used for lifting the back plate is arranged on the bottom face of the nursing bed body, and rotating rods are symmetrically installed on the two sides of the nursing bed body. A supporting column is rotatably installed on the outer side of the rotating rod, a second groove is formed in the end, away from the rotating rod, of the supporting column, the second groove extends in the width direction of the nursing bed body and penetrates through the two sides of the supporting column, a shaft rod is fixedly installed in the second groove, a transverse plate is rotatably installed on the outer side of the shaft rod, and a pull rope is fixedly installed in the transverse plate. The device has the advantages that the back plate is used for supporting a pa